1987
DOI: 10.1203/00006450-198707000-00012
|View full text |Cite
|
Sign up to set email alerts
|

Protein Deprivation from the Neonatal Period Impairs Lung Development in the Rat

Abstract: ABSTRACT. The effects of early protein-deficiency on lung development were studied in the rat. Newborn male rats were nursed in groups of eight. Control dams and pups received a 15% protein diet during the whole experiment. Test mothers only received 12 and 8% proteins from the 7th and the 14th day of lactation. Test rats fed a diet of 8% protein were weaned at 21 days and maintained on the low protein diet for 1 month. This caused a marked decrease in body weight gain, but lung/body weight ratio was not affec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0
3

Year Published

1989
1989
2025
2025

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 9 publications
1
17
0
3
Order By: Relevance
“…Lungs of rats fed on a diet restricted in protein from the neonatal period had decreased recoil pressure (6), whereas protein restriction from d 28 resulted in a moderately increased recoil pressure (7). Inasmuch as we know from the observations of Myers et al (8) rats produces an increase in lung elastin concentration, our second experiment could lend support to their conclusions.…”
supporting
confidence: 65%
See 4 more Smart Citations
“…Lungs of rats fed on a diet restricted in protein from the neonatal period had decreased recoil pressure (6), whereas protein restriction from d 28 resulted in a moderately increased recoil pressure (7). Inasmuch as we know from the observations of Myers et al (8) rats produces an increase in lung elastin concentration, our second experiment could lend support to their conclusions.…”
supporting
confidence: 65%
“…We had previously observed that proteindeficient rats, although fed ad libitum with an isocaloric diet, reduced their food intake so that their calorie consumption was about 30% less than that of the controls; their protein intake was reduced by 65% (6). Thus the anomalies observed in the present study might result from a mixed protein-energy deficiency with a predominant protein deficit similar to the most common form of malnutrition of children in developing countries.…”
Section: Discussionmentioning
confidence: 41%
See 3 more Smart Citations